Presupposition and Women’s Language: Women’s Empowerment in Asma Elbadawi’s Utterances in Social Media - Rahmani, Niswah Qintara; Sulaeman, Dedi; Assiddiqi , Hasbi (Institut Agama Islam Negeri Palopo, 2025)
This study examines linguistic strategies in conveying women's empowerment messages through social media, specifically Instagram and YouTube. This study combines women's language theory by Robin Lakoff and presupposition theory by George Yule. The method used is descriptive qualitative with purposive sampling technique, focusing on posts and statements that contain elements of women's empowerment. The results show various features of women's language such as lexical hedges, intensifiers, and empty adjectives, as well as various types of presuppositions such as existential and factive presupposition, which implicitly reinforce empowerment narratives. This study shows how language on social media can shape powerful social discourses about women's identities and struggles.